MENGUKUR KEPUASAN PASIEN RUMAH SAKIT ISLAM SITI RAHMAH PADANG ATAS KUALITAS PELAYANAN INSTALASI FARMASI DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS - Deta Aulia; Rahmiati Rahmiati; Gesit Tabrani (Universitas Negeri Padang, 2019)
This study aims to analyze and find out: (1) The service quality of pharmaceutical installations provided by RSI Siti Rahmah Padang is in accordance with patient expectations using the Importance Performance Analysis method (2) Service attributes that need to be prioritized to improve the quality of pharmacy installation services to patients in Siti Rahmah Padang Hospital using the Cartesian diagram. The study population was all visitors or patients who visited to get treatment at a pharmacy pharmacy installation. The sampling technique of this study was to use the accidental sampling method with a total sample of 100 people.The data used is primary data. The data analysis technique uses the Importance Performance Analysis method using Microsoft Excel software. The results showed that: (1) There are 1 service attribute that have a positive gap that is able to meet customer satisfaction (2) There are 3 service attributes that are the top priority for immediate improvement (3) Factors to improve the quality of pharmaceutical services caused by human factors , material, method, and environment.Keywords: Service Quality, Importance Performance Analysis, customer satisfaction, fishbone